Peristiwa Black Swan Pandemi Covid-19 : Dampak Kasus Pada Kinerja Saham Bursa Efek Indonesia - Nandra Hary Wiguna; Nyoman Ayu Wulan Trisna Dewi (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to determine the impact of Covid-19 on the performance of Indonesian Stock Exchange shares. This study uses data on positive infected cases, recoveries, and deaths related to Covid-19, as well as the JCI closing price in 2020. The data collected is in the form of secondary data. This type of research is an event study with regression data analysis techniques. The results of this study indicate that positive confirmed cases and recovered have an effect on stock performance on the Indonesia Stock Exchange. While the case of death does not affect the performance of shares on the Indonesia Stock Exchange. So, this information is expected to be able to contribute in the form of information, especially to investors and potential investors as material for consideration in making decisions to invest in the following year. This is important because the Covid-19 pandemic has not ended so far. The information that will be generated can be used as a basis for analysis in order to avoid losses and maximize returns. Keywords : Covid-19, Stock Performance, Indonesia Stock Exchange